The problem of the subjective side of the crime of killing and abusing animals under the act of august 21, 1997 on the protection of animals - Fijałkowska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The aim of the article is to discuss the crimes of killing and abusing animals set out in the Animal Protection Act. The characteristics of the subjective side of the analyzed acts were analyzed. Attention was drawn to the problem related in particular to the subject of the crime of animal abuse. The positions of the representatives of the criminal law doctrine and views appearing in the jurisprudence, especially of the Supreme Court, were presented.